UPAYA PENINGKATAN KANDUNGAN MINYAK ATSIRI PADA BAWANG MERAH VARIETAS TUK-TUK DENGAN PERLAKUAN BERBAGAI MACAM DOSIS PUPUK KIMIA PABRIKAN - Rifqi Adisonda; Bagus Nur Rochman; Bayu Handoko (UNU Purwokerto, 2022)
The aims of the study are to determine the effect of various manufactured chemical fertilizers on the increase of the essential oil content in Tuk-tuk and to determine which treatment is best to increase the essential oil content of this particular variety of shallots. The study used a non-factorial randomized block design with three treatments, and each was repeated nine times. The treatments' dosages were B1: ZA 50kg/ha; Urea 25kg/ha; SP36 250kg/ha and KCl 25kg/ha, B2: ZA 100kg/ha; Urea 50kg/ha; SP36 300kg/ha and KCl 50kg/ha, B3: ZA 150kg/ha; Urea 100kg/ha; SP36 350kg/ha and KCl 100kg/ha. The growth and yield observation variables in this study were the number of leaves (fruit), plant height (cm), leaf area (cm2), tuber diameter (cm), fresh plant weight (g), dry plant weight (g), fresh tuber weight (g), dry tuber weight (g), essential oil content (%). The data obtained were analyzed using the F-test, and then the data showed a significant effect proceeded with the DMRT test at a level of 5%. The results of the F-test on the shallots' observed growth and yield variables were not significantly affected by the treatment of manufactured chemical fertilizer. Meanwhile, B3K5 treatment with B3 dose: ZA 150kg/ha; Urea 100kg/ha; SP36 350kg/ha, and KCl 100kg/ha were the best treatments to increase the essential oil content in the Tuk-tuk variety.